A122: Metabolomic Analysis of Breath Volatile Organic Compounds Reveals Unique Breathprints in Children With Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Zeft, Andrew; Costanzo, Denise; Alkhouri, Naim; Patel, Nishaben; Grove, David; Spalding, Steven J.; Dweik, Raed
Abstract : Background/Purpose: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of diseases characterized by synovial inflammation and is the most common rheumatic complaint in children. Breath testing is becoming an important diagnostic method to evaluate many disease states. The aim of this study was to analyze exhaled volatile organic compounds (VOCs) to evaluate for the presence of a unique breath pattern to differentiate pediatric patients with JIA from healthy controls. Methods: This was a prospective cross‐sectional, single‐center study that included pediatric JIA patients and healthy controls (age range, 5–21 years). The diagnosis of JIA was determined using standard clinical criteria. Exhaled breath was collected and analyzed using a selective ion flow tube (SIFT‐MS) to identify new markers of JIA. Results: 76 patients were included in the study (21 with JIA and 55 healthy controls). JIA phenotype was as follows: 12 polyarticular RF negative, 2 persistent oligoarticular, 4 extended oligoarticular, 2 psoriatic, and 1‐ enthesitis‐related arthritis. Routinely analyzed VOCs for SIFT‐MS quantification showed significant differences in 13 VOCs peaks between JIA patients and healthy controls. Discriminant analysis via stepwise variable selection of mass scanning ion peak data demonstrated that 4 VOCs can classify patients with JIA or as healthy controls with only three misclassifications; p < 0.001. Further analysis revealed that breath 1‐decene, 1‐octene, and 3‐methyhexane (all markers of oxidative stress) were significantly higher in the JIA group compared to controls (11.5 ± 6.7 ppb vs. 2.1 ± 0.2 for 1‐decene; 10.5 ± 2.2 vs. 4.5 ± 0.7 for 1‐octene; and 17.5 ± 3.7 vs. 10.4 ± 1.4 for 3‐methyhexane, p value < 0.001 for all). Conclusion: Exhaled breath analysis is a promising non‐invasive method to distinguish children with JIA from healthy children. We provide pilot data to support the hypothesis that a unique breathprint can be demonstrated for JIA in the exhaled metabolome.